Analysis of the relationship between financial policy-competitiveness capacity - economic growth: A study of economic transformation in Vietnam - Daniel , Balsalobre-Lorente; Pham, Minh Tien; Dinh, Thi Thu Hien (Journal of Finance - Marketing Research, 2024)
This study aims to examine the relationship between fiscal policy, provincial competitiveness and Vietnam’s economic growth. The study uses the VECM model for time series data including the factors Total tax revenue of the country, Growth of the expanded money supply represents fiscal policy; Provincial competitiveness and Vietnam’s economic growth in the period 1990-2021. The study has provided additional empirical evidence on the relationship between financial policy, provincial competitiveness and economic growth in the context of selecting Vietnam. The research results show that financial policies have affected economic growth in localities in the third period with an impact of 3%. In comparison, provincial competitiveness has affected economic growth right in the 1st period with a large impact of 18%. The change of economic growth has an impact in the same direction with provincial-level financial and energy competitiveness policies. From this result, the authors propose implications to limit the lag in the implementation of financial policies.